Pemberdayaan petani lokal melalui pelatihan pembuatan pupuk organik dan pestisida nabati kepada kelompok tani Suku Meyah: Empowering local farmers through training on making organic fertilizer and organic pesticides for the Meyah Tribe Farmer Groups - Rumainum, Inna Martha; Tuhumena, Veronica L.; Mariay, Ivonne F.; Budiyono, Budiyono; Karamang, Syukur; Andriyani, Liz Y.; Purnomo, D. Wasgito; Chadikun, Paulus; Wamafma, Ilona M. (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  Farmers from the Meyah tribe have the potential for empowerment in the context of agricultural development in the West Papua region. The aim of this training is to provide an understanding of organic farming and improve the ability of farmers from the Meyah tribe in making organic fertilizers and organic pesticides. The methods used in this training are discussion and practice. In the discussion session, the PKM Faperta team presented material on horticultural plant cultivation, organic farming, flower and fruit stimulation, as well as organic fertilizers and organic pesticides. Participants were very enthusiastic about listening to the material presented and asked many questions related to the obstacles faced in farming. In the practical session, participants were facilitated to make organic pesticides made from soursop leaves and garlic. Then proceed with making organic goat manure fertilizer. Both methods were very effective because they aroused enthusiasm in the community which could be seen from response given.  Keywords: Farmers; Meyah tribe; Organic fertilizer; Organic pesticide   ABSTRAK Petani asal suku Meyah memiliki potensi pemberdayaan dalam rangka pengembangan pertanian di wilayah Papua Barat. Tujuan dari pelatihan ini ialah untuk memberikan pemahaman tentang pertanian organik dan meningkatkan kemampuan petani asal suku Meyah dalam membuat pupuk organik dan pestisida nabati. Metode yang digunakan dalam pelatihan ini ialah diskusi dan praktek. Pada sesi diskusi, tim PkM Faperta menyajikan materi tentang budidaya tanaman hortikultura, pertanian organik, perangsangan bunga dan buah, serta pupuk organik dan pestisida nabati. Peserta sangat antusias menyimak materi yang disajikan dan memberikan banyak pertanyaan terkait kendala yang dihadapi dalam bercocoktanam. Pada sesi praktek, peserta difasilitasi untuk membuat pestisida nabati berbahan baku daun sirsak dan bawang putih. Kemudian dilanjutkan dengan pembuatan pupuk organik kotoran kambing. Kedua metode yang dilakukan sangat efektif karena membangkitkan antusiasme masyarakat yang dapat dilihat dari respon yang diberikan. Kata kunci: Petani; Pestisida nabati; Pupuk organik; Suku Meyah